Evaluación del servicio brindado por el área de avalúos y catastros a usuarios externos del Gobierno Autónomo Descentralizado del cantón Sucre - Jaramillo Alcívar, María Jacqueline (2021)
This research is developed based on events that occur in the world, in cantons such as Sucre, where public institutions such as the Autonomous Decentralized Government of the canton, there are shortcomings in terms of the quality of service, which reduces satisfaction external users, that is why this problem arises. The research details the process of the survey, the reasons that led the authors to carry it out, and other important aspects for its improvement, such as the problem statement, objectives, and methods used, including several methods that allowed investigating and obtain relevant data on the service offered by the Appraisals and Cadasters area to external users, find the causes related to the investigation; and techniques focused on the subject EVALUATION OF THE SERVICE PROVIDED BY THE AREA OF APPRAISALS AND ASSESSMENTS TO EXTERNAL USERS OF THE DECENTRALIZED AUTONOMOUS GOVERNMENT IN SUCRE CANTON. Likewise, it was possible to capture the data obtained from the observation file, the field visit, the survey designed with the Servqual model and its five dimensions, the interview, conclusions, recommendations and annexes that present information to support the problem. It is concluded that user dissatisfaction is caused by events that decrease the quality of the service and that are generating negative effects on customer service.